Hepatoma-Targeted Radionuclide Immune Albumin Nanospheres: 131I-antiAFPMcAb-GCV-BSA-NPs - Mei Lin; Junxing Huang; Dongsheng Zhang; Xingmao Jiang; Jia Zhang; Hong Yu; Yanhong Xiao; Yujuan Shi; Ting Guo (Analytical Cellular Pathology)
An effective strategy has been developed for synthesis of radionuclide immune albumin nanospheres (131I-antiAFPMcAb-GCV-BSA-NPs). In vitro as well as in vivo targeting of 131I-antiAFPMcAb-GCV-BSA-NPs to AFP-positive hepatoma was examined. In cultured HepG2 cells, the uptake and retention rates of 131I-antiAFPMcAb-GCV-BSA-NPs were remarkably higher than those of 131I alone. As well, the uptake rate and retention ratios of 131I-antiAFPMcAb-GCV-BSA-NPs in AFP-positive HepG2 cells were also significantly higher than those in AFP-negative HEK293 cells. Compared to 131I alone, 131I-antiAFPMcAb-GCV-BSA-NPs were much more easily taken in and retained by hepatoma tissue, with a much higher T/NT. Due to good drug-loading, high encapsulation ratio, and highly selective affinity for AFP-positive tumors, the 131I-antiAFPMcAb-GCV-BSA-NPs are promising for further effective radiation-gene therapy of hepatoma.